What Families Need and Physicians Deliver - Contrasting Communication Preferences between Surrogate Decision-Makers and Physicians during Outcome Prognostication in Critically-Ill TBI Patients - Quinn, Thomas (Neurocrit Care, 2017)
INTRODUCTION: Surrogate decision-makers (“surrogates”) and physicians of incapacitated patients have different views of prognosis and how it should be communicated, but this has not been investigated in neurocritically-ill patients. We examined surrogates’ communication preferences and physicians’ practices during the outcome prognostication for critically-ill traumatic brain injury (ciTBI) patients in two level-1 trauma centers and seven academic medical centers in the U.S. METHODS: We used qualitative content analysis and descriptive statistics of transcribed interviews to identify themes in surrogates (n=16) and physicians (n=20). RESULTS: The majority of surrogates (82%) preferred numeric estimates describing the patient’s prognosis, as they felt it would increase prognostic certainty, and limit the uncertainty perceived as frustrating. Conversely, 75% of the physicians reported intentionally omitting numeric estimates during prognostication meetings due to low confidence in family members’ abilities to appropriately interpret probabilities, worry about creating false hope, and distrust in the accuracy and data quality of existing TBI outcome models. Physicians felt that these models are for research only and should not be applied to individual patients. Surrogates valued compassion during prognostication discussions, and acceptance of their goals-of-care decision by clinicians. Physicians and surrogates agreed on avoiding false hope. CONCLUSION: We identified fundamental differences in the communication preferences of prognostic information between ciTBI patient surrogates and physicians. These findings inform the content of a future decision aid for goals-of-care discussions in ciTBI patients. If validated, these findings may have important implications for improving communication practices in the neuroICU independent of whether a formal decision aid is used.